Discursive construction of identities in a social network-educational space: Insights from an undergraduate Facebook group for a linguistics course. (August 2017) - Chau, Dennis; Lee, Carmen
Highlights: Discursive resources and practices are studied in a Facebook group created for an undergraduate course. Both academically-related and socially-related discourse functions are found in this 'social network-educational space'. Members construct various identities in the space with the discursive resources and practices. Abstract: This article reports on a study of a Facebook group created for a linguistics course at a university in Hong Kong. It examines the discursive resources and practices identified in the group, as well as discusses how identities are constructed through hybrid discourse. Informed largely by discourse-centered online ethnography, we observed the group and its discourse systematically, and contacted the group members. Specifically, we collected screen data with a view to identifying the discourse functions and analyzing the linguistic resources deployed by the members. Semi-structured interviews, incorporating the elements of techno-biography and stimulated recall, were conducted to delve into the practices and identity construction. The study argues that the group is not merely an academic group, but a "social network-educational space" in that both academically-related and socially-related discourse functions could be observed. The members were found to deploy a wide range of resources such as emoticons for meaning making. This article then presents a case of a participant which illustrates how various identities could be constructed with the discursive resources and practices. It concludes by advancing our understanding of concepts such as the community of practice and considering the implications for future computer-mediated discourse research.